Evaluation of deep eutectic solvent as a new monomer for molecularly imprinted polymers for removal of bisphenol A - Hussain Shah, Syed Asim; Asman, Saliza
Deep eutectic solvent molecularly imprinted polymer (DES-MIP) was synthesized by bulk polymerization via free radical polymerization using bisphenol A (BPA) as a template, DES as a functional monomer, ethylene glycol dimethyl acrylate (EGDMA) as a crosslinker and benzoyl peroxide as initiator. DES functional monomer was prepared by the combination of choline chloride methacrylic acid (ChCl-MAA). The synthesized DES-MIP was then compared with conventional molecularly imprinted polymer (MIP) synthesized using methacrylic acid (MAA) as a functional monomer. The DES-MIPhas a higher selectivity for BPA (17.72 mg/g) than competing chemicals, including bisphenol AP (9.78 mg/g), 2-naphthol(8.25), and 4-tertiary butyl-phenol (6.98 mg/g). The optimization parameters include the effects of pH, adsorption kinetics,adsorption isotherm, and thermodynamic studies were investigated. DES-MIP showed the highest binding capacity at pH7. The kinetic and isotherm studies demonstrated good agreement with a pseudo-second-order kinetic model and Langmuirisotherm models, respectively. The thermodynamic study proved that the adsorption of BPA on DES-MIP was exothermic and spontaneous with ΔH0 (-23.734×kJ/mol) and ΔG0 (-2.929 kJ/mol−). Reusability experiments show that the DES-MIP can be recycled five times without significantly diminishing its adsorption capacity. As a result, it proved that the contribution of DES as a functional monomer alternative in MIP synthesis considerably improved the recognition of BPA adsorption.